2022
DOI: 10.1200/op.21.00904
|View full text |Cite
|
Sign up to set email alerts
|

Human Epidermal Growth Factor Receptor 2–Targeting Approaches for Colorectal Cancer: Clinical Implications of Novel Treatments and Future Therapeutic Avenues

Abstract: The treatment paradigm for colorectal cancer (CRC) has changed significantly over the past decade with targeted therapeutics. Human epidermal growth factor receptor 2 ( HER2) amplification is seen among 3%-4% of patients with metastatic CRC (mCRC). The biological discovery of HER2 amplification in cancer cells has led to practice-changing drug development for several solid tumors, including breast, gastric, and esophageal cancers. HER2 amplification is now highly actionable in CRC with distinct therapeutic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…This is seen in approximately 3–4% of patients with CRCLM, especially in RAS-RAF wild-type tumours. It is associated with shorter survival [ 40 , 41 ]. In these types of patients, dual HER2-targeting is recommended, with a combination of trastuzumab with pertuzumab, tucatinib or lapatinib [ 40 ].…”
Section: Impact Of the Metastasis Molecular Pattern In The Choice Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This is seen in approximately 3–4% of patients with CRCLM, especially in RAS-RAF wild-type tumours. It is associated with shorter survival [ 40 , 41 ]. In these types of patients, dual HER2-targeting is recommended, with a combination of trastuzumab with pertuzumab, tucatinib or lapatinib [ 40 ].…”
Section: Impact Of the Metastasis Molecular Pattern In The Choice Of ...mentioning
confidence: 99%
“…It is associated with shorter survival [ 40 , 41 ]. In these types of patients, dual HER2-targeting is recommended, with a combination of trastuzumab with pertuzumab, tucatinib or lapatinib [ 40 ].…”
Section: Impact Of the Metastasis Molecular Pattern In The Choice Of ...mentioning
confidence: 99%
“…Several ongoing clinical trials are exploring anti-ERBB2 therapies that evaluate the efficacy of small molecule inhibitors, ADCs, and their combination with established therapies [ 84 ].…”
Section: Clinical Trials For Patients With Erbb2-positive Mcrcmentioning
confidence: 99%
“…In the companion to this editorial, Karan et al 1 present a clinical review of the progress made in targeting HER2 amplification in advanced colorectal cancer (CRC). Although multiple phase III randomized controlled trials have shown the benefit of targeting HER2 amplifications in patients with breast and esophagogastric cancer, the optimal treatment regimen and sequencing of HER2 -directed treatment for patients with HER2 -amplified CRC is less clear.…”
mentioning
confidence: 99%